Chief of this River: Zhaawni-binesi and the Chenail Ecarté lands - Fehr, Rick; Macbeth, Janet; Sands Macbeth, Summer (Ontario History)

(untitled) (The Ontario Historical Society, 2019)
The narratives of European settlement in Canada have largely excluded the presence of Indigenous peoples on contested lands. This article offers an exploration of an Anishinaabeg community and a regional chief in early nineteenth century Upper Canada. The community known as the Chenail Ecarté land, and Chief Zhaawni-binesi, have become historically obscure. Through the use of primary documents the authors explore the community’s history, its relocation, and Chief Zhaawni-binesi’s role in the War of 1812 and in community life. Ultimately, the paper charts the relocation of the community in the face of mounting settler encroachment. The discussion attempts to increase knowledge and appreciation of Indigenous history in Southwestern Ontario.